2020
DOI: 10.3390/su12093687
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Spatiotemporal Dynamics of Land Use Changes in Four Municipalities of China Based on Intensity Analysis

Abstract: Land use/cover change (LUCC) is becoming one of the most important and interesting problems in the study of global environmental change. Identifying the spatiotemporal behavior and associated driving forces behind changes in land use is crucial for the regional sustainable utilization of land resources. In this study, we consider the four municipalities of China (Beijing, Tianjin, Shanghai, and Chongqing) and compare their spatiotemporal changes in land use from 1990 to 2015 by employing intensity analysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Furthermore, we also noted that during the period from 2010 to 2015, the total amount of land conversion in Yunnan Province decreased, the land was relatively stable, and the growth intensity of construction land was lower than in the other two periods (2005 to 2010 and 2015 to 2020). Tong et al observed a similar trend in the intensity of land use change for four municipalities directly under the control of the Central Government of China [63]. This can be explained by the impact of government policies on land change.…”
Section: Ple Land and Esv Changesmentioning
confidence: 73%
“…Furthermore, we also noted that during the period from 2010 to 2015, the total amount of land conversion in Yunnan Province decreased, the land was relatively stable, and the growth intensity of construction land was lower than in the other two periods (2005 to 2010 and 2015 to 2020). Tong et al observed a similar trend in the intensity of land use change for four municipalities directly under the control of the Central Government of China [63]. This can be explained by the impact of government policies on land change.…”
Section: Ple Land and Esv Changesmentioning
confidence: 73%
“…Land use dynamics are an indicator for evaluating the change rate and amplitude of different land use types within a certain time range [40]. They also reflect the impact of human activities on a single land use type.…”
Section: Single Dynamic Degree Of Land Usementioning
confidence: 99%
“…Regarding the processes of LULCCs, they have witnessed the quantity and degree of changes, the direction of transfer, and the spatial patterns [19]. Because LULCCs in different regions have different contributions and responses to global changes, regionalscale LULCC studies tend to focus on key regions and hot spots, such as megacities and watersheds [20][21][22]. As a complete natural geographical unit, a river basin is crucial to human survival and sustainable social and economic development.…”
Section: Introductionmentioning
confidence: 99%